1990
DOI: 10.1002/hep.1840110416
|View full text |Cite
|
Sign up to set email alerts
|

Excessive In Vitro Bacterial Lipopolysaccharide–Induced Production of Monokines in Cirrhosis

Abstract: The objective of this study was to analyze monokine production by peripheral blood mononuclear cells from patients with alcoholic cirrhosis. The capacity of peripheral blood mononuclear cells and purified monocytes from these patients to produce tumor necrosis factor alpha, interleukin 1 beta, and interleukin 6 was investigated. Spontaneous production of tumor necrosis factor alpha, interleukin 6 and interleukin 1 beta was similar in cirrhotic and healthy subjects, but serum levels of interleukin 6 (less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
71
3
4

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(87 citation statements)
references
References 43 publications
9
71
3
4
Order By: Relevance
“…Reported studies show that ALC is associated with depressed secretion of IL1 (27,48,49) and TNFa (27,49) by both LPS-stimulated PB monocytes (27) and macrophages (49), which is even more pronounced among patients with severe ALC and malnutrition (48,49). In contrast, others have found an increased secretion of IL1 (50) and TNFa (50,51) by LPS-stimulated PB monocytes from ALC patients. Additionally, a close relationship between severity of ALC (Child-Pough score B or C) and the elevation of the expression of both the TNF and TNF-receptor genes in PB mononuclear cells has been observed (52).…”
Section: Discussionmentioning
confidence: 98%
“…Reported studies show that ALC is associated with depressed secretion of IL1 (27,48,49) and TNFa (27,49) by both LPS-stimulated PB monocytes (27) and macrophages (49), which is even more pronounced among patients with severe ALC and malnutrition (48,49). In contrast, others have found an increased secretion of IL1 (50) and TNFa (50,51) by LPS-stimulated PB monocytes from ALC patients. Additionally, a close relationship between severity of ALC (Child-Pough score B or C) and the elevation of the expression of both the TNF and TNF-receptor genes in PB mononuclear cells has been observed (52).…”
Section: Discussionmentioning
confidence: 98%
“…The development of less severe degrees of pulmonary edema may result from poor immune function 14,15 and increased levels of proinflammatory mediators. 16,17 Malnutrition may also be important, although it has been shown that pulmonary edema may occur in patients with liver dysfunction despite correction of vascular oncotic pressures. 18 In our study, no patient had radiological evidence of interstitial pulmonary edema preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PBMCs from patients with cirrhosis after resting in vitro for 24 hours produce TNF-␣ levels similar to those of healthy controls. 26 It may be that this primed state in patients with cirrhosis may overcome the proposed mechanism of inhibition by calcineurin inhibitors. The inhibition of TNF-␣ production by dexamethasone is likely to be a different mechanism unaffected by liver disease.…”
Section: Discussionmentioning
confidence: 99%